Painless Obstructive Jaundice Secondary to a Common Bile Duct Abscess: A Delayed Sequela of Cholecystectomy. (21st December 2009) - Fairhurst, Katherine; Strickland, Andrew; Bridgewater, Franklin H. G.; Maddern, Guy J.
Abstract : Complications related to cholecystectomy are well described. Most occur in the early postoperative period and are recognised either at the time of, or shortly after surgery. Clinical sequelae occurring years following cholecystectomy are rare and infrequently reported. In addition, most delayed complications are related to the continuing presence or new formation of gallstones. In this paper we present a unique case of an abscess of the common bile duct wall, presenting with painless obstructive jaundice more than 30 years following an open cholecystectomy, without the presence of gallstones. The clinical presentation, investigations, and treatment are discussed with a review of other relevant reported cases in the literature.